Characterization, antioxidant activity, and mineral profiling of Auricularia cornea mushroom strains - Khan, Asif Ali; Lu, Li-Xin; Yao, Fang-Jie; Fang, Ming; Wang, Peng; Zhang, You-Min; Meng, Jing-Jing; Ma, Xiao-Xu; He, Qi; Shao, Kai-Sheng; Wei, Yun-hui; Xu, Baojun (Frontiers in Nutrition, 2023)
Background Mushrooms are considered as next-generation healthy food components. Owing to their low-fat content, high-quality proteins, dietary fiber, and rich source of nutraceuticals. They are ideally preferred in formulation of low-caloric functional foods. In this view, the breeding strategies of mushroom Auricularia cornea (A. cornea) focusing on high yield and higher quality with rich nutritional values and health benefits are still needed. Materials and methods A total of 50 strains of A. cornea were used to analyze the bio efficiency and the time required for fruiting body formation following the cultivation experiment. The calorimetric method was used to evaluate the antioxidant activity and quantify the crude polysaccharides and minerals content thereafter. Results The results showed that the time required for fruiting body formation and biological efficiency varied significantly among the selected strains. Noticeably, the wild domesticated strain Ac13 of A. cornea mushroom showed the shortest fruit development time (80 days). Similarly, the hybrid strains including Ac3 and Ac15 possessed the highest biological efficiency (82.40 and 94.84%). Hybrid strains Ac18 (15.2%) and cultivated strains Ac33 (15.6%) showed the highest content of crude polysaccharides, while cultivated strains Ac1 and Ac33, demonstrated the highest content of total polysaccharides in the fruiting body (216 mg. g−1 and 200 mg. g−1). In the case of mineral content, the highest zinc contents were observed from the cultivated strain Ac46 (486.33 mg·kg−1). The maximum iron content was detected from the hybrid strain Ac3 (788 mg·kg−1), and the wild domesticated strain Ac28 (350 mg·kg−1). The crude polysaccharides of the A. cornea strain showed significant antioxidant potential, and the ability of Ac33 and Ac24 to scavenge DPPH radicals and ABTS, which was significantly improved compared to other strains, respectively. Principal component analysis was applied to examine the agronomic traits and chemical compounds of various strains of A. cornea mushrooms. The results revealed that cultivated, wild domesticated, and hybrid strains of A. cornea exhibited distinct characteristics in terms of growth, yield, and nutritional properties. Conclusion The crude polysaccharides from A. cornea mushroom strains act as natural antioxidants, the wild, hybrid, and commercial A. cornea mushroom strains can achieve rapid growth, early maturation, and high yields. The evaluation of biochemical indexes and nutritional characteristics of strains with excellent traits provided a scientific basis for initiating high-quality breeding, provided germplasm resources for the production of “functional food” with real nutritional and health value.